Correlation between serum galectin‐9 levels and liver fibrosis. Issue 2 (26th January 2018) - Fujita, Koji; Niki, Toshiro; Nomura, Takako; Oura, Kyoko; Tadokoro, Tomoko; Sakamoto, Teppei; Tani, Joji; Yoneyama, Hirohito; Morishita, Asahiro; Kuroda, Noriyuki; Arai, Takeshi; Nishimoto, Naoki; et al.
Abstract: Background and Aim: Chronic liver diseases progress from chronic inflammation to fibrosis to tumorigenesis. Galectin‐9, a β‐galactoside‐specific animal lectin, is indicated to contribute to all three steps of progression. The aim of this study was to determine which of the three steps was most dominant in elevating the serum galectin‐9 concentration and to test the possibility of galectin‐9 as a serum biomarker. Methods: Japanese patients with chronic hepatitis, liver cirrhosis, hepatocellular carcinoma (HCC), non‐alcoholic fatty liver disease, or alcoholic liver disease who provided informed consent were enrolled in this study. Serum galectin‐9 levels were measured using a sandwich ELISA. Multiple regression analyses were performed usingezr to identify factors that determined serum galectin‐9 concentration. Results: One hundred one patients with 50 of chronic hepatitis and 51 of liver cirrhosis were enrolled; the cohort included 45 cases of hepatitis C virus infection, 13 cases of hepatitis B virus infection, and 46 cases with HCC‐related complications. The median serum galectin‐9 concentration was 77.54 pg/mL (interquartile range: 18.89–241.9 pg/mL). Multiple linear regression analyses proved Fibrosis‐4 index and aspartate aminotransferase to platelet ratio index, indexes of liver fibrosis, were able to predict the serum galectin‐9 levels with statistical significance. A multiple logistic regression analysis determined 10 pg/mL increase in the serum galectin‐9 concentration presented an odds ratio of 3.90 for liver fibrosis progression. Conclusions: The serum galectin‐9 concentration represents a potential biomarker of liver fibrosis in patients with chronic liver diseases, regardless of chronic inflammation or the presence of HCC complications. Furthermore, higher serum galectin‐9 levels are a predictor for liver fibrosis progression.